Kemampuan Menulis Teks Deskripsi dalam Bahasa Makassar Menggunakan Media Lingkungan Siswa Kelas VIII SMP Negeri 1 Polobangjeng Utara Kabupaten Takalar: The Ability to Write Descriptive Texts in Makassar Language Using Environmental Media of Class VIII Students of SMP Negeri 1 Polobangjeng Utara, Takalar Regency - Syam, Nur Annisa; Daeng, Kembong; Rahim, Abd (Journal Studies in Indonesian Language and Literature, 2025)
This study aims to describe the ability to write descriptive texts in Makassar language using environmental media for class VIII students of SMP Negeri 1 Polongbangkeng Utara, Takalar Regency. This study is a quantitative descriptive study. The research variable is the ability to write descriptive texts. The population in this study were 235 class VIII students of SMP Negeri 1 Polongbangkeng Utara, Takalar Regency. The results showed that the results of the student assessment who obtained a KKM (Minimum Completion Criteria) score of 75-100 were 2 people with a percentage of 7% and did not reach the set criteria, which was 75%. While students who achieved scores below the KKM (Minimum Completion Criteria) 0-74 were 28 people with a percentage of 93%. This can be seen in the ability to write descriptive texts in Makassar language using environmental media for class VIII students of SMP Negeri 1 Polongbangkeng Utara, Takalar Regency are in the category of unable.